Animal Metaphors in Iwan Fals’ Social Critics and Humanity Songs: Ecolinguistics Study - Mutia Mawaddah Rohmah; Oktavianus Oktavianus; Fajri Usman (IAIN MADURA, 2019)
Language and ecology have a reciprocal relationship in Ecolinguistics perspective. One of the relationships is formed through the metaphorical expression containing the names of fauna(animal metaphors). This study described the animal metaphors found in Iwan Fals’ Social Critics and Humanity songs that very famous among Indonesian community. Through Ecolinguistics study, the writer tried to find out how animal as a part of ecosystem can be used to describe human life especially their social and political life through metaphorical frames. This is a descriptive-qualitative research that is conducted by using Ecolinguistics parameters consists of interrelationship, diversity and environment parameters to analyze the interactions between language and ecology. The result of analysis showed that the metaphorical expression formulated and generated from the characteristic of the nature of fauna (animal metaphors) that found in Indonesian environment. The nature used as a source domain was mapped to a target domain referred to human beings with their activities forming a new understanding and enrich vocabulary. The connection between the two domains was recorded in cognitive of the language users at the ideological dimension which is then understood by society at the sociological dimension. The whole meaning formed a strong relationship between language and environment.